Pancreatic serine protease extraction by affinity partition using a free triazine dye - Rocha, María Victoria (2012)
Afﬁnity partitioning combines the partitioning behavior of biological macromolecules in aqueous two phase systems with the principle of biorecognition. Among the numerous substances that have been evaluated as ligands, the reactive dyes constitute a group of low cost textile dyes which have proved to act as biomimetic ligands formany enzymes. The ability of reactive yellow 2 (RY2)to interact with trypsin (TRP) and chymotrypsin (ChTRP) and its behavior in aqueous two-phase systems formed by polyethylene glycol (PEG) and sodium citrate (NaCit) ? were investigated. Different variables such as PEG molecular weight, tie line length and dye concentration were analyzed. RY2 showed to bind speciﬁcally to both TRP and ChTRP with afﬁnity constants near to 10 3M−1. Its partition equilibrium is practically displaced to the top phase in systems formed by PEG of differentmolecular weight. Addition ofthis dye to PEG 8000/NaCit systems until a ﬁnal concentration of 0.196% (w/w) induced an increase in TRP and ChTRP partition coefﬁcients of at least 2 times over that in the absence of the ligand. These ﬁndings demonstrate that RY2 fulﬁls all the requirements to be considered as an afﬁnity ligand in aqueous two-phase partitioning of TRP and ChTRP.